Chondrodysplasias With Multiple Dislocations Caused by Defects in Glycosaminoglycan Synthesis - Dubail, Johanne; Cormier-Daire, Valérie (Frontiers in Genetics, 2021)
Chondrodysplasia with multiple dislocations form a group of severe disorders characterized by severe pre and postnatal growth retardation, joint laxity and dislocations of large joints, hand anomalies and/or vertebral anomalies. The majority of chondrodysplasias with multiple dislocations has been linked to pathogenic variants in genes encoding glycosyltransferases, sulfotransferases and transporters implicated in the synthesis or sulfation of glycosaminoglycans, long and unbranched polysaccharides composed of repeated disaccharide bond to protein core of proteoglycan. Glycosaminoglycan biosynthesis is a tightly regulated process that occur mainly in the Golgi and that require coordinate action of numerous enzymes and transporters as well as adequate Golgi environment. Any disturbances of this chain of reactions will lead to incapacity of cell to construct correct glycanic chains. This review focuses on genetic and glycobiological studies of chondrodysplasias with multiple dislocations associated with glycosaminoglycan biosynthesis defects and related animal models. A deep understanding of the molecular mechanisms of those disorders, mostly through deep phenotyping of in vitro and/or in vivo models is essential for the development of new biomarkers for clinical screenings and innovative therapeutics for these diseases.